1998
DOI: 10.1089/neu.1998.15.307
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Increases Neurological Damage and Behavioral Deficits From Post-Traumatic Secondary Ischeie Insults

Abstract: The effects of post-traumatic administration of glucose 2.0 g/kg was compared to saline infusion with and without control of brain temperature at 37 degrees C on behavioral and histological measures of brain injury after controlled cortical impact injury complicated by a secondary ischemic insult. The glucose infusion increased blood glucose concentration from 114 +/- 4 to 341 +/- 76 mg/dl prior to the secondary ischemic insult. The resulting outcome measures were significantly worse in the glucose infusion gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…Therefore, swimming latency was chosen as the only paradigm for cognitive assessment in the water maze test. With the balloon expansion model, it was possible to provoke reproducible cognitive deficits as known from other vessel occlusion (Alexis et al, 1995;Jaspers et al, 1990) or trauma models (Cherian et al, 1998;Dixon et al, 1998;Hamm et al, 1992;Markgraf et al, 2001). Cognitive deficits improved over the whole observation time in noncooled animals, but swimming latencies remained clearly prolonged compared to controls or hypothermic animals.…”
mentioning
confidence: 97%
“…Therefore, swimming latency was chosen as the only paradigm for cognitive assessment in the water maze test. With the balloon expansion model, it was possible to provoke reproducible cognitive deficits as known from other vessel occlusion (Alexis et al, 1995;Jaspers et al, 1990) or trauma models (Cherian et al, 1998;Dixon et al, 1998;Hamm et al, 1992;Markgraf et al, 2001). Cognitive deficits improved over the whole observation time in noncooled animals, but swimming latencies remained clearly prolonged compared to controls or hypothermic animals.…”
mentioning
confidence: 97%
“…11 Similarly, methylprednisolone-induced hyperglycemia may contribute to secondary neurologic injury. Animal models have demonstrated that hyperglycemia is an important contributor to secondary neurologic injury, 12,25 and hyperglycemia has been implicated as a contributor to poor neurologic outcome in humans. 26,27 For example, Lam et al 27 observed that head-injured patients with a postoperative blood glucose concentration greater than 200 mg/dl had a significantly worse neurologic outcome than did patients with a lower blood glucose concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the incidence of wound infection, sepsis, pneumonia, and the duration of intensive care unit stay are all increased in patients receiving high-dose methylprednisolone. [5][6][7][8] Importantly, some methylprednisolone-mediated morbidities/side effects put patients at increased risk of complications known to contribute to secondary neurological injury (eg, sepsis-induced hypotension, [9][10][11] glucocorticoid-medicated hyperglycemia 12 ). Consequently, methylprednisolone-related side effects may actually work at crosspurposes to any salutary neurological benefits of methylprednisolone therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This could enhance susceptibility to infection and also might exacerbate secondary brain injury. [33][34][35] Tight glycemic control may be warranted, although the recent work by Vespa and associates suggests caution and use of insulin at higher glucose levels of probably more than 150 mg/dL. 36 Drug metabolism is profoundly altered by hypothermia.…”
Section: Complications Associated With Therapeutic Hypothermiamentioning
confidence: 99%